Vitamin D and its receptor polymorphisms: New possible prognostic biomarkers in leukemias - Seyed Mohammad Sadegh Pezeshki; Ali Amin Asnafi; Abbas Khosravi; Mohammad Shahjahani; Shirin Azizidoost; Saeid Shahrabi (Frontiers Media S.A., 2018)
Several factors such as chromosomal translocations, gene mutations, and polymorphisms are involved in the pathogenesis of leukemia/lymphoma. Recently, the role of vitamin D (VD) and vitamin D receptor (VDR) polymorphisms in hematologic malignancies has been considered. In this review, we examine the possible role of VD levels, as well as VDR polymorphisms as prognostic biomarkers in leukemia/lymphoma. Relevant English language literature were searched and retrieved from Google Scholar search engine (1985-2017). The following keywords were used: vitamin D, vitamin D receptor, leukemia, lymphoma, and polymorphism. Increased serum levels of VD in patients with leukemia are associated with a better prognosis. However, low VD levels are associated with a poor prognosis, and VDR polymorphisms in various leukemias can have prognostic value. VD biomarker can be regarded as a potential prognostic factor for a number of leukemias, including acute myeloblastic leukemia (AML), chronic lymphoblastic leukemia (CLL), and diffuse large B-cell lymphoma (DLBCL). There is a significant relationship between different polymorphisms of VDR (including Taq I and Fok I) with several leukemia types such as ALL and AML, which may have prognostic value.